Manajemen Proyek Sistem Informasi Untuk Pengembangan MDA Content Archive Platform - Ifrah Ayyuna (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
This document is a project proposal plan for the creation or development of applications by PT. Multi Development Application (MDA) through the MDA Content Archive Platform (CAP) solution which accommodates and optimizes paper-based, digital data storage (Application Optimized Storage) for the benefit of banking organizations, the private sector, government, educational institutions and all kinds of business entities, which have The desire to realize a real form of cooperation in efforts to protect data or archives that have high historical value, so that the data or archives are safe and not easily damaged.